DEVELOPING SPEAKING SKILLS IN PRIMARY SCHOOL THROUGH NON-TRADITIONAL TECHNOLOGIES (Academicia Globe: Inderscience Research, 2023)
At present, in teaching a foreign language, the primary task is to master the skill of speaking in this language. In the educational system of many countries, including the Republic of Uzbekistan, the teaching of a foreign language has been introduced into the primary school curriculum. This thesis discusses some aspects of improving speaking in primary grades with the help of non-traditional technologies.